Revolusi Industri 4.0: Big Data, Implementasi Pada Berbagai Sektor Industri (Bagian 2) - Mantik, Hari; Awaludin, Muryan (Universitas Dirgantara Marsekal Suryadarma, 2023)
Big Data is a concept in which the characteristics of the amount of data (volume), variety of data (variety) and speed (velocity) are managed with sophisticated and state-of-the-art technology through data analytic tools with the aim of generating, identifying and forecasting future opportunities in increasing personalization to society or customers, increasing productivity, assisting strategic decision making, shortening system life cycles, and driving change towards a more positive one.